Depolymerization of waste polycarbonates to value-added products - Padhi, Ganeshdev; Pansare, Vaibhav Ramachandra; Bajpai, Priyam; Krishna, Gamidi Rama; Vanka, Kumar; Barsu, Nagaraju (ChemSusChem, 2025)
Additive free aminolysis method developed for the depolymerization/upcycling of polycarbonates. We report here chemical recycling of polycarbonate under ambient conditions to get its monomer bisphenol A, monoaminocarbamate and biscarbamates in 1 : 2 : 1 ratio respectively. By employing the secondary amine as the aminating reagent, facilitates the depolymerization to work under additive/catalyst free conditions. The developed method deals with depolymerization of waste polycarbonates and works even with late-stage amine derivatives such as amoxapine and desloratadine which are drugs molecules known to treat neurotic disorders and allergies respectively. The reaction can be scaled up and works with similar efficacy which depicts the efficiency of the depolymerization of wasteend-of-life polycarbonate plastic waste. The biscarbamate and bisphenol-A was further subjected for the post functionalization to obtain amides and phenol in good yields. Developed additive/catalyst free aminolysis of waste polycarbonates to carbamates and monomer BPA at ambient conditions. Variety of secondary amines were screened including the late stage amine derivatives like amoxapine and desloratadine which delivered the expected products successfully. Later the developed methodology was even applied for the different end-of-life polycarbonates with the secondary amine and achieved the depolymerization without any obstacle. Further carried out the scale up reaction and derivatization of carbamates and BPA to amide and phenol synthesis. image
Keywords: Aminolysis; carbamates; depolymerization; End-of-life; Polycarbonate